Knowledge, attitude, and practice of healthcare professionals toward sarcopenia - Bing Liang; Beibei Wang; Jingbing Liang; Xiaoning Sun (Scientific Reports)
Abstract To explore the knowledge, attitude, and practice (KAP) of healthcare professionals toward sarcopenia. A multicenter, cross-sectional study was conducted at Hainan Hospital of P.L.A General Hospital between May 23 and June 20 2024, involving healthcare professionals. Demographic information and KAP scores were collected through a self-administrated questionnaire. A total of 557 valid questionnaires were analyzed (453 females), achieving a validity rate of 89.98%. Mean scores indicated knowledge at 8.39 ± 2.74, attitude at 27.60 ± 2.71, and practice at 34.69 ± 10.78. Multivariate logistic regression analysis revealed that knowledge score (OR = 1.296, P < 0.001), attitude score (OR = 1.507, P < 0.001), male gender (OR = 2.001, P = 0.013), age (OR = 1.042, P = 0.026), and the number of sarcopenia patients seen (11–50 cases: OR = 3.124; 50 + cases: OR = 4.289, both P < 0.001) were independently associated with proactive practice. Structural equation modeling demonstrated significant positive direct effects of knowledge on both attitude (β = 0.869, P < 0.001) and practice (β = 2.385, P < 0.001), as well as attitude on practice (β = 0.378, P = 0.001). Healthcare professionals showed inadequate knowledge and practice regarding sarcopenia; targeted interventions are necessary to enhance understanding and promote proactive engagement.